2017
DOI: 10.1515/mjss-2017-0052
|View full text |Cite
|
Sign up to set email alerts
|

Academic Cheating in School: A Process of Dissonance Between Knowledge and Conduct

Abstract: Academic cheating behavior in schools have (r = -.0.096, p = 0.260) and between knowledge of cheating behavior with the behavior appearance (r = -0.08, p = 0.925). However, there was a difference on the appearance of plagiarizing behavior reviewed from the knowledge of plagiarism (F = 2.303, p = 0.038) while there was no difference on cheating behavior reviewed from the knowledge of cheating (F = 1.18, p = 0.355). This showed that the frequency of students conducting cheating or plagiarizing behavior was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
1
4
0
1
Order By: Relevance
“…The findings of this study have vividly demonstrated that there is a high prevalence of academic cheating among high school students. The 80.5% of the prevalence rate found in this study is in line with findings worldwide (e.g., Decoo & Colpaert, 2002;Galloway, 2012;Jensen et al, 2002;McCabe et al, 2001;Pramadi et al, 2017;Šimić Šašić & Klarin, 2009). Academic cheating behaviors of "copying answers from nearby friends"; 'let others to copy mine; "taking crib notes to exam halls"; "whispering answers to nearby friends" and 'giving answers to friends by signals were found to be the top five forms of cheating in which majority of students reported to engage in actively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this study have vividly demonstrated that there is a high prevalence of academic cheating among high school students. The 80.5% of the prevalence rate found in this study is in line with findings worldwide (e.g., Decoo & Colpaert, 2002;Galloway, 2012;Jensen et al, 2002;McCabe et al, 2001;Pramadi et al, 2017;Šimić Šašić & Klarin, 2009). Academic cheating behaviors of "copying answers from nearby friends"; 'let others to copy mine; "taking crib notes to exam halls"; "whispering answers to nearby friends" and 'giving answers to friends by signals were found to be the top five forms of cheating in which majority of students reported to engage in actively.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with this finding, McCabe (2001) andO'Rourke et al (2010) reported that copying from student exam papers and allowing other student to copy is the most common type of cheating students admitted to engage in. A recent study by Pramadi et al (2017) also found out that copying answers from friends are the most common cheating in high schools. Well performing students also seems willing to support their friends cheat (Stevenson-Clarke & Brimble, 2007).…”
Section: Discussionmentioning
confidence: 92%
“…35 for an overview). Comparable levels of dishonesty among upper secondary students have been reported from several other countries, including Spain (Sureda-Negre et al 2015 ), Indonesia (Pramadi et al 2017 ) and Slovenia (Šorgo et al 2015 ). Widespread cheating and corruption has been reported among Cambodian secondary students (Brehm 2016 ), while a survey of Taiwanese students reported markedly lower levels of plagiarism (Chang et al 2015 ).…”
Section: Introductionmentioning
confidence: 82%
“…The academic world is currently the highlight as the result of many academic fraud cases committed by lecturers and students individually. These phenomena prove that individual behavior in committing academic fraud like plagiarism or others is not merely determined by an individual's level of knowledge [1] . One variable expected to be correlated with academic fraud is an individual's moral development.…”
Section: Introductionmentioning
confidence: 83%